Matthew : Paideia Commentaries on the New Testament - Talbert, Charles H. (Grand Rapids, Mich. : Baker Academic, 2010)
A leading New Testament scholar examines cultural context and theological meaning in Matthew. This commentary approaches each text in its final, canonical form, proceeding by sense units rather than word-by-word or verse-by-verse. Each sense unit is explored in three sections: (1) introductory matters, (2) tracing the train of thought, (3) key hermeneutical and theological questions--From publisher description.
Birth narratives -- Pt. 1. Jesus's ministry begins -- Pt. 2. Jesus's authority is revealed -- Pt. 3. Jesus's ministry creates division -- Pt. 4. Jesus focuses on his disciples -- Pt. 5. Jesus and judgement. -- Passion and resurrection narrative.
Includes bibliographical references (p. 325-345) and indexes.
Keywords: Bible. -- Commentaries; Mathew Greek Text Commentaries -- Mathew Interpretation